Thinking the Repatriation of African Audiovisual Heritage with the 1980 UNESCO Recommendation: The Contributions of an Old Intergovernmental Debate (1974–1991) - (:unkn) unknown (My University, 2022)
While the audiovisual heritage held by France and related to its former colonies in Africa has not entirely been returned to the African States, this article seeks to revisit the production and assessment process of the 1980 UNESCO Recommendation for the safeguarding and preservation of moving images. This international instrument in fact includes provisions related to audiovisual recordings produced during the colonial period, the terms of which deserve to be reexamined in the light of the new technological and political context.
Keywords: African Research